The mediating effect of brand satisfaction on the relationship between brand personality and brand loyalty: Evidence from Malaysia - Mabkhot, Hashed Ahmed; Md. Salleh, Salniza; Shaari, Hasnizam (Growing Science, 2016)
This study empirically investigates the mediating effect of brand satisfaction on the relationship between brand personality and brand loyalty among Malaysian customers toward local automobile brands (Proton and Perodua).Four hypotheses were developed to test hypothesizing relationships between brand personality and brand satisfaction on brand loyalty.The data were collected from consumers of automobile brands in north Malaysia peninsula from three states which were Kedah, Penang, and Perlis. This study applies partial least squares to a sample of 458 customers to test hypothesized relationships.The findings indicate that brand personality and brand satisfaction appear to have a positive and significant relationship with brand loyalty.Moreover, brand satisfaction was found to be a mediator in the relationship between brand personality and brand loyalty. The results are compared with earlier findings and implications for further research are discussed.